Comparison Between Supraclavicular and Infraclavicular Approach in Subclavian Vein Catheterization in Tertiary Center of Nepal - Khapung, Robin; Pokharel, Jeju Nath; KC, Kiran Kumar; Pradhan, Kripa; Gurung, Uma; Basnyat, Subi; Giri, Praveen Kumar (Journal of Karnali Academy of Health Sciences, 2020)
Introduction: Central vein catheterization can be introduced in subclavian vein (SCV), internal jugular vein or femoral vein for volume resuscitation and invasive monitoring technique. Due to anatomical advantage and lesser risk of infection subclavian vein is preferred. Either supraclavicular (SC) or infraclavicular (IC) approach could be used for subclavian vein catheterization. The aim of the study was to compare SC and IC approach in ease of catheterization of SCV and record the complications present if any. Methods and materials: This was a hospital based comparative, interventional study conducted from November 2016 to October 2017 in Operation Theater in Bir Hospital. In this study, 70 patients for elective surgical cases meeting the inclusion criteria were randomly enrolled. Then samples were equally divided by lottery into either supraclavicular or infraclavicular approach groups. The Access time, cannulation success rate, attempts made for successful cannulation of vein, easy insertion of catheter and guide wire, approximate inserted length of catheter and associated complications in both groups were recorded. Data was entered in statistical software SPSS 16. Chi-square test was used. P value < 0.05 was considered significant. Results: The mean access time in group SC for SCV catheterization was 2.12 ± 0.81 min compared to 2.83 ± 0.99 min in group IC (p-value= 0.002). The overall success rate in catheterization of the right SCV using SC approach (34 / 35) was better as compared with group IC (33 / 35) using IC approach. First successful attempt in the SC group was 74.28% as compared with 57.14% in the IC group. Conclusion: The SC approach of SCV catheterization can be considered alternative to IC approach in terms of landmark accessibility, success rate and rate of complications.